Effect of Spirulina Platensis on Liver Malondialdehyde Levels of Male White Rat Induced by High Dose Paracetamol - Anggilia Vanny; Sihning E. J. Tehupuring; Indri Ngesti Rahayu; Roostantia Indrawati (Universitas Wijaya Kusuma Surabaya, 2023)
Paracetamol is widely used in therapy, yet it becomes hepatotoxic agent in a high dose using. The CYP450 enzyme metabolizes a small portion of paracetamol to a reactive substance, NAPQI. High dose of paracetamol causes an extensive increase in NAPQI levels. NAPQI then binds to hepatocytes conditions of oxidative stress. Spirulina platensis contains C-phycocyanin, flavonoids, and phenolics that inhibit lipid peroxidation and reduce oxidative stress. This study aims to determine the effect of Spirulina platensis on MDA levels in the liver tissue of male Wistar rats induced by high dose of paracetamol. This research was experimental with a Randomized Post-test Only Control Group design using 24 white male rats divided into three groups; negative control group (G-), positive control group (G+) was given paracetamol at a dose of 1,250 mg/kg on the 8th day, and treatment group (Gt) was given an amount of Spirulina platensis extract 360 mg/kg BW/day for ten days from 1st until 10th day and paracetamol at a single dose of 1,250 mg/kg BW on the 8th. At the 10th day of the treatment, all groups were terminated for liver tissue collection. TBA test was used to calculate MDA levels. Statistical tests analyzed the results of the data. This statistical tests by SPSS software: MDA levels in the treatment group did not significantly differ (p = 0.144) compared to the negative control group. There was a significant difference of liver tissue MDA levels in the treatment group (p = 0.016) compared to the positive control group. This study concludes that administering Spirulina platensis at a dose of 360 mg/kg/day for ten days can help prevent on increase in tissue MDA levels and maintain liver conditions close to their original state.